120 - FACTORS THAT INTERFERES IN ACTIONS AND CONTROL OF THE LEPROSY IN THE USER´S PERSPECTIVE IN RIO GRANDE DO NORTE (Fiep Bulletin - online, 2011)
This study has an objective identifies the factors that interferes in the actions and control of the leprosy in the state of Rio Grande do Norte under the users perspective. The study is characterized by being an operational research. The population's study was composed by 61 users in active registration in the year of 2006. The data were consolidated and analyzed by the program MICROSOFT OFFICE Excel. After analysis we presented those factors: accessibility difficulty to the units of health with resolution, the belated diagnosis of the disease, the reference difficulty and against-reference, anti-leprosy medications lack in the municipal districts and medications anti-reactionaries, deficiency in the orientations and lack of the professionals of health domain about the actions of PCH.
Keywords: leprosy; control program; elimination; nursing